Simulations of the mu+SR experiment - Lancaster, T; Shiroka, T (2006)
We present the results of simulations of the mu+SR experiment using the GEANT4 toolkit, PENELOPE and other numerical calculations. We show the effects of applying large magnetic fields on the trajectory and polarization of the incoming muon beam and on the paths of the outgoing positron ensemble. Simulations are also presented investigating the use of highly segmented position-sensitive detectors as a possible solution to event concentration at a particular angle which can occur at high fields. (c) 2005 Elsevier B.V. All rights reserved.